Revitalisasi Paradigma Kefilsafatan dalam Tradisi Akademik Perguruan Tinggi Keagamaan Islam - Umam, Fawaizul (TEOSOFI: Jurnal Tasawuf dan Pemikiran Islam, 2015)
This article proposed to revitalize a philosophical paradigm in the academic tradition of Islamic Higher Education (IHE) as a scientific endeavor to pave the way for the revival of Islamic civilization. IHE was selected because its academic tradition institutionally is more likely to hold it than other Islamic educational institutions such as pesantren that tends to play a ?prophetic? role as the guardian of religious orthodoxy. The revitalization held to establish three agendas, namely (1) terminating the dichotomous epistem-ology and then moving on an integrative epistemology, (2) applying multidisciplinary approaches in scientific activities, and (3) strengthening the spirit of criticism and freedom of thought as fundamental principles of the scientific dynamics. Due to the academic traditions concerning intellectual praxis, the agendas have to paint the scientific activities in IHE, from design of sciences to norms of intellectual promiscuity. Establishing three agendas into the academic tradition paradigmatically will enable IHE to creat significant contributions to the revival of Islamic civilization in the future.